Analysis of Public Attitudes and Willingness to Implement Renewable Energy in Households to Reduce GHG Emissions in Indonesia - Feinnudin, A Agung; Suhud, Usep; Hamidah (Formosa Journal of Sustainable Research, 2024)
This study explores household attitudes and willingness to adopt renewable energy in Indonesia to reduce GHG emissions. Key factors include public awareness, economic barriers, policy clarity, and behavioral resistance. Surveys and statistical analyses reveal that awareness boosts adoption, while high costs and skepticism hinder it. Targeted interventions, such as education campaigns, financial incentives, and community engagement, are essential to address these barriers, offering actionable insights for policymakers and stakeholders to advance sustainable energy transition efforts